Imperial urbanism in the borderlands : Kyiv, 1800-1905 - Bilenʹkyĭ, Serhiĭ (Toronto : University of Toronto Press, 2018)
"In the nineteenth and early twentieth century Kyiv was an important city in the European part of the Russian empire, rivaling Warsaw in economic and strategic significance. It also held the unrivaled spiritual and ideological position as Russia's own Jerusalem. In Imperial Urbanism in the Borderlands, Serhiy Bilenky examines issues of space, urban planning, socio-spatial form, and the perceptions of change in imperial Kyiv. Combining cultural and social history with that of urban studies, Bilenky unearths a wide range of unpublished archival materials and argues that the changes experienced by the city prior to the revolution of 1917 were no less dramatic and traumatic than those of the Communist and post-Communist era. In fact, much of Kyiv's contemporary urban form, architecture, and natural setting were shaped by imperial modernizers during the long nineteenth century. The author also explores a general culture of imperial urbanism in Eastern Europe. Imperial Urbanism in the Borderlands is the first work to approach the history of Kyiv from an interdisciplinary perspective and showcases Kyiv's rightful place as a city worthy of attention from historians, urbanists, and literary scholars."--
Mapping the city in transition -- Using the past : the great cemetery of Rus' -- Municipal autonomy under the Magdeburg law, 1800-1835 -- Planning a new city : empire transforms space, 1835-1870 -- Municipal autonomy reloaded : space for sale, 1871-1905 -- Counting Kyivites : the language of class, religion, and ethnicity -- Municipal elites and "urban regimes" : continuities and disruptions -- Sociospatial form and psychogeography -- What language did the monuments speak?
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Urbanization -- Ukraine -- Kyïv -- History -- 19th century; Urbanization -- Ukraine -- Kyïv -- History -- 20th century; Kyïv (Ukraine) -- History -- 19th century; Kyïv (Ukraine) -- History -- 20th century; Urbanisation -- Ukraine -- Kiev -- Histoire -- 19e siècle.; Urbanisation -- Ukraine -- Kiev -- Histoire -- 20e siècle.; Kiev (Ukraine) -- Histoire -- 19e siècle.; Kiev (Ukraine) -- Histoire -- 20e siècle.; HISTORY -- Europe -- Eastern; HISTORY -- Europe -- Former Soviet Republics; HISTORY -- Europe -- Russia & the Former Soviet Union; Urbanization; Ukraine -- Kyïv; 1800-1999; History